'What Exactly are We a Part of Now?' Norwegian NGOs' Engagement with State Governmentality. Issue 3 (2nd September 2019) - Ofstad, Sverre; Marin, Andrei
Abstract: Non-governmental Organizations (NGOs) have risen to the forefront of the development sector. Yet, for a group of development actors that are explicitly non-governmental, it is conspicuous that their rise to prominence owes itself to state funding. This conundrum has spurred a debate about whether NGOs represent the poor and marginalized, or the states that funds them. This debate is highly topical today as donor states increasingly conflate development policy with other policy fields, a process often referred to as 'the new humanitarianism'. Here, we contribute to this debate by exploring the relationship between Norwegian humanitarian NGOs and the Norwegian state. Through semi-structured interviews with 10 Norwegian NGOs, we investigated how the state and NGOs influence each other. By using a Foucauldian approach to the study of governance, we find that the state shapes NGOs by orienting their activities towards professionalism and quantifiable targets. NGOs, however, are not passive, but continuously try to mold the structures of their relationship with the state in a plethora of ways. Nonetheless, the new humanitarianism is inserting a new rationality into the Norwegian aid system, where NGOs reorient their activities to achieve security and foreign policy objectives. As a result, many Norwegian NGO workers find their activities compromised. The new humanitarianism, with its potential for a holistic approach to development, has instead undermined the practices of Norwegian NGOs.